ENHANCING RELIGIOUS TOLERANCE IN THE INDONESIAN CONTEXT: EXPLORING DIGITAL MEDIA INITIATIVES BY GOVERNMENT AND NON-GOVERNMENTAL ENTITIES - A QUALITATIVE CASE STUDY - Sopiana, Yunita; Judijanto, Loso; Muhammad, A Fadel; Halilurrahman, Halilurrahman; Erliani, Saadah (CV. Adiba Aisha Amira, 2023)
This qualitative case study investigates the intricate interplay of digital media initiatives undertaken by government and non-governmental entities in Indonesia to promote religious tolerance. Indonesia's diverse religious landscape provides a captivating backdrop for this research. Government bodies have harnessed digital media to bolster transparency, accountability, and interfaith dialogue, while non-governmental organizations (NGOs) assume roles as advocates, watchdogs, and proponents of religious diversity awareness. The study critically assesses the effectiveness of these initiatives and their influence on spiritual perceptions and interfaith interactions. It underscores the pivotal role of the Indonesian context in shaping these endeavors, offering insights that extend not only to Indonesia but also to the broader global context, emphasizing the importance of fostering religious tolerance in our interconnected world.